VARIATION IN THE PHYSICO–MECHANICAL PROPERTIES OF GRANITIC AGGREGATES IN OGUN STATE, NIGERIA (Nigerian Journal of Technology, 2018)
Coarse aggregate is an essential constituent of concrete constituting about 60% to 80% of concrete depending on the mix ratio. Granite is reported to be the most widely distributed plutonic rock in the earth crust. It is predominantly available in various parts of Ogun State of Nigeria. Its different properties have been known to strongly influence the fresh and hardened state properties of concrete. In this study, samples of four different sizes of granites (9.5mm, 12.5mm, 19mm and 25mm) were obtained from four different quarry sites across the state. The Physical properties such as specific gravity, moisture content and water absorption and the Mechanical properties such as aggregate impact value and aggregate crushing value of the samples were evaluated. The results of the specific gravity, moisture content and water absorption vary from 2.61 to 2.86, 0.69 to 1.22%, 0.16 to 2.13% respectively. While the aggregate impact value and aggregate crushing value vary from 18.30 to 28.12% and 6.21 to 9.45% respectively. It was therefore concluded that there are variations in the physical and mechanical properties of granites produced in Ogun State of Nigeria. The observed variations occur in relation to the various sizes and for the different quarry sites.     http://dx.doi.org/10.4314/njt.v37i4.4VARIATION IN THE PHYSICO–MECHANICAL PROPERTIES OF GRANITIC AGGREGATES IN OGUN STATE, NIGERIA